An observational study on clinical and bacteriological profile of new-borns with early onset sepsis - Tharu, Mobin George; Santhakumar, Rati; Manoj, V. C. (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal sepsis related mortality is preventable with timely recognition, rational antimicrobial therapy and aggressive supportive care. The objective of this study was to study the maternal and neonatal risk factors in new-borns with early onset sepsis and to ascertain commonest pathogen responsible. Methods: This study was done in the neonatal intensive care unit tertiary care hospital, Thrissur. Data collected after clinical examination and from the records of new-borns diagnosed with early onset sepsis were analyzed. All neonates suspected to have sepsis had a septic screen to corroborate the diagnosis. Blood culture was performed in all cases of suspected sepsis prior to starting antibiotics. The risk factors for sepsis, both maternal and neonatal were analysed. Their clinical features and bacteriological profile were studied. Data analysis was done using their mean±standard deviation (SD), percentage analysis, chi-square test or fischer’s test. Results: Fifty newborns with diagnosed early onset sepsis (EOS) were studied. Results suggest that maternal screening is prudent, interventions like vaginal examination were causative of sepsis than meconium stained liquor or prolonged rupture of membranes. A coincidental finding suggests that sepsis is more common in males and term babies. Blood culture showed predominant pathogen to be Klebsiella. Conclusions: Among the maternal factors, increased frequency of vaginal examination was most prevalent in the study group. Prematurity and asphyxia were not strong pre-runners for sepsis. EOS cases presenting with respiratory distress were 50%. Fever and tachycardia were the next common clinical features. The cases yielded blood culture positive were 20% and Klebsiella pneumonia (40%) was the commonest organism isolated.